Integrating performance assessments across a PK-20 continuum: A locally developed collaboration - Kathryn McCurdy; Emilie Mitescu Reagan; Audrey Rogers; Thomas Schram (Arizona State University, 2018)
A response to Stosich et al.'s (2018) article reviewing ways in which states have taken up performance assessments, this commentary seeks to extend the focus and use of performance assessments to preservice teacher education. As such, the authors describe statewide initiatives in New Hampshire that are working to integrate performance assessments along a PK - 20 continuum by articulating how Stosich et al.'s key points of educator capacity, context, and assessments for and of learning are developing in one state. This commentary highlights key contextual factors for the lasting implementation of the performance assessments as well as raises critical new challenges and opportunities for understanding this tool as an assessment for and of learning.